Widespread Prevalence of Plasmid-Mediated Colistin Resistance Gene mcr-1 in Escherichia coli from Père David's Deer in China - Xiaoyu Lu (American Society for Microbiology, 2020)
ABSTRACT Père David’s deer (Elaphurus davidianus or milu) is an endangered species, and the prevalence of antimicrobial resistance (AMR) such as mcr-1-positive strains among them has been unknown. In this study, we aimed to investigate the genomic characterizations of mcr-1-positive strains and provide insight into the dissemination of AMR in nature reserve settings. Sixty-seven mcr-1-positive Escherichia coli isolates from 97 fecal samples were identified by PCR and found resistant to colistin. The prevalence of β-lactam resistance was very high, and there were 64 mcr-1-positive isolates containing β-lactamase genes. Transconjugants of 66 mcr-1-positive isolates were acquired through conjugation experiments. PCR-based replicon typing (PBRT) showed that 44 strains harbored IncI2 mcr-1-bearing plasmids, eight strains harbored IncX4 mcr-1-carrying plasmids, and 14 strains harbored IncHI2 mcr-1-positive plasmids. Notably, mcr-1 was located in the chromosome of LD27-1. Clonal dissemination and horizontal dissemination of mcr-1 by plasmids coexist. We first report the prevalence of plasmid-mediated mcr-1 in E. coli from Père David’s deer in China. mcr-1-bearing IncI2 plasmid was the most frequent plasmid type, and the first IncI2 plasmid harboring both blaCTX-M-132 and mcr-1 is characterized here. Our results support the implication of Père David’s deer as a potential reservoir for MCR-1-producing E. coli. IMPORTANCE The mcr-1 gene is widely reported around the world and has been identified on various plasmids with different replicon types. Resistance to the last-line antibiotic colistin mediated by mcr-1 still represents a threat to global public health. Père David’s deer is a highly endangered species originating in China, and many deer are currently being raised in captivity for gradual reintroduction to the wild. If this species carries AMR bacteria, it will pose a potential threat to the environment. Therefore, research on the dissemination of mcr-1-positive E. coli from Père David’s deer is of great significance. This is the first study to investigate the microbiological and genomic surveillance of MCR-1-producing bacteria colonized among Père David’s deer in China, and we uncovered a high prevalence of MCR-1-producing E. coli. The importance of constant surveillance for AMR bacteria in nature reserve settings is emphasized.